2014
DOI: 10.1063/1.4868587
|View full text |Cite
|
Sign up to set email alerts
|

Precipitation of iron in multicrystalline silicon during annealing

Abstract: In this paper, the precipitation kinetics of iron in multicrystalline silicon during moderate temperature annealing are systematically studied with respect to annealing time, temperature, iron super-saturation level, and different types and densities of precipitation sites. The quantitative analysis is based on examining the changes in the concentrations and distributions of interstitial iron in multicrystalline silicon wafers after annealing at 400–700 °C. This is achieved by using the photoluminescence imagi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
39
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 47 publications
4
39
0
Order By: Relevance
“…The finding that interstitial iron is gettered by SiN x films may help explain the discrepancy between the results of long, low temperature annealing experiments performed on multicrystalline silicon (mc-Si) by Krain et al, 37 Liu and Macdonald, 9 and Al-Amin and Murphy. 12 Krain et al 37 used SiN x passivation and found a systematic reduction in interstitial iron, with the activation energy being close to the diffusion activation energy of iron.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…The finding that interstitial iron is gettered by SiN x films may help explain the discrepancy between the results of long, low temperature annealing experiments performed on multicrystalline silicon (mc-Si) by Krain et al, 37 Liu and Macdonald, 9 and Al-Amin and Murphy. 12 Krain et al 37 used SiN x passivation and found a systematic reduction in interstitial iron, with the activation energy being close to the diffusion activation energy of iron.…”
Section: Discussionmentioning
confidence: 66%
“…3(a)), most likely due to an insufficient degree of supersaturation of interstitial iron at 700 C and an insufficient time of 30 minutes for the nucleation and growth of iron silicide. 1,9,25 The SIMS iron profiles also show that the SiO 2 layer is unlikely to have served as a segregation gettering layer for iron, as the iron concentration in SiO 2 remains below the detection limit. This agrees with the work by Smith et al, 44 where the solubilities of iron in Si and SiO 2 were found to be similar.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The plot on the left shows that this occurs even far away from the grain boundaries, indicating precipitation at defects within the grains, as detailed elsewhere [24,25]. This precipitation at intra-grain defects is the most important in reducing the global dissolved Fe concentration during low temperature annealing, since the intra-grain regions account for a large majority of the wafer surface.…”
Section: Solid State Phenomena Vols 205-206mentioning
confidence: 90%
“…Extensive research has been performed into external gettering using phosphorus, boron, or aluminium to remove metallic impurities from the bulk [7][8][9]. A number of studies have also been performed into low temperature internal gettering in which metallic impurities are redistributed within the material in configurations in which they are less detrimental to average lifetime [10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%